If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 + 6z = 4 + 12z Solving 22 + 6z = 4 + 12z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-12z' to each side of the equation. 22 + 6z + -12z = 4 + 12z + -12z Combine like terms: 6z + -12z = -6z 22 + -6z = 4 + 12z + -12z Combine like terms: 12z + -12z = 0 22 + -6z = 4 + 0 22 + -6z = 4 Add '-22' to each side of the equation. 22 + -22 + -6z = 4 + -22 Combine like terms: 22 + -22 = 0 0 + -6z = 4 + -22 -6z = 4 + -22 Combine like terms: 4 + -22 = -18 -6z = -18 Divide each side by '-6'. z = 3 Simplifying z = 3
| 11ab^2c^3-55a^3b^2c=0 | | 10x-9-3x=10 | | x^2-46x+180=0 | | 3=7-2y | | 1/3y+1=1/2y-3 | | 0.4(1+6c)= | | X^2-2y+x=0 | | z^6+5=8-z^6 | | 8-2x+1=9x+9 | | x+3+5=2x+4 | | 6x+3-5=40 | | 10(x+1)+8(x-1)=x-8 | | 4(2x-1)-6(3-x)=8 | | -5x+9y=-18 | | 3n^2+8=10n | | Mx+nx=x | | -2n+2n=6(1+6n)+7(1-7n) | | -5(0)+9y=-18 | | r-(-1)=9 | | 9(3n+3)=7(2n+4)+6 | | 6(x+8)-x=5x+4 | | -2(t-5)+4t=9t-6 | | 2x-9=2x-45 | | x(x+5)=(2x+10)(x-2) | | 5y-5+11x-1=9x+21 | | 15n-5=n+325 | | X^2+x=2y | | 9-(6y+2x)=8(x-y) | | 1+.80z=2+.75z | | 9*1+3=y | | 3y=32+5y | | 7w-11-4w=6 |